1998
DOI: 10.1080/095530098142338
|View full text |Cite
|
Sign up to set email alerts
|

The signal model: a possible explanation for the conversion of DNA double-strand breaks into chromatid breaks

Abstract: Chromatid breaks in human cells represent the apparent interstitial loss of up to about 40 Mbp of DNA, difficult to account for as single lesions under the classical 'breakage-and-reunion' hypothesis. If breakage-first resulted from two interacting DNA double-strand breaks (dsb) with the loss or displacement of the intervening fragment, a dose-squared relationship would be predicted for chromatid breaks. However, the relationship between chromatid break frequency and dose for human cells is linear. The alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…It is known that some chromatid breaks involve interactions between chromatin strands of sister chromatids, that is, inter-chromatid rearrangements, and it has been proposed that these interactions could involve misjoining at the cross-over points of large looped domains (eg Harvey and Savage, 1997). Such rearrangements can be visualised using harlequin (fluorescence plus giemsa; FPG) staining, and result in the appearance of colour switches between chromatids at the break-points that occur at a frequency of approximately 16% (eg Harvey and Savage, 1997;Bryant, 1998). It is thought that the remainder results from intrachromatid rearrangements, as described above.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that some chromatid breaks involve interactions between chromatin strands of sister chromatids, that is, inter-chromatid rearrangements, and it has been proposed that these interactions could involve misjoining at the cross-over points of large looped domains (eg Harvey and Savage, 1997). Such rearrangements can be visualised using harlequin (fluorescence plus giemsa; FPG) staining, and result in the appearance of colour switches between chromatids at the break-points that occur at a frequency of approximately 16% (eg Harvey and Savage, 1997;Bryant, 1998). It is thought that the remainder results from intrachromatid rearrangements, as described above.…”
Section: Discussionmentioning
confidence: 99%
“…British Journal of Cancer (2008) Human response to low doses of ionising radiation shows a wide variation as exemplified by the different frequencies of radiationinduced chromatid breaks observed in metaphase chromosomes in phytohaemagglutinin-stimulated peripheral blood T-lymphocytes (PBL) from different normal individuals and sporadic cancer cases, and elevated frequencies of such chromatid breaks have been linked to cancer susceptibility (Scott et al, 1994(Scott et al, , 1996Roberts et al, 1999;Baria et al, 2001Baria et al, , 2002Buchholz and Wu, 2001;Riches et al, 2001;Papworth et al, 2001;Smart et al, 2003;Baeyens et al, 2002Baeyens et al, , 2005. Using a short time interval (1-2 h) between radiation exposure and sampling, the metaphase cells (blocked with colcemid) collected are those that were in the G2-phase of the cell cycle at the time of exposure and show frequent chromatid breaks (discontinuities or terminal deletions) that have been shown to be induced as a linear function of radiation dose (Bryant, 1998).Cell-cycle arrest is a factor that could possibly influence observed frequencies of chromatid breaks, and at least one study of human tumour cell lines in vitro (Schwartz et al, 1996) reports an inverse relationship between mitotic inhibition and chromatid break frequency. Also, using premature chromosome condensation (PCC) in G2-phase cells with phosphatase inhibitor calyculin, G2 cells were distinguished from normal mitotic metaphases by their split centromeres and by the loss of centromeric constriction (Terzoudi et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NHEJ is more important for repairing g-radiation induced dsb during G1-early S-phase, while HR is preferentially used for repair in late S-G2 phase (Takata et al, 1998;Rothkamm et al, 2001). Although recent studies have shown that G0/G1 chromosomal aberrations are essentially the result of misrepaired dsb (Wu et al, 1996;Boei et al, 2000;Fomina et al, 2000) by the NHEJ repair system (Jeggo, 1998;Takata et al, 1998;Rothkamm et al, 2001), the mechanisms involved in the formation of G2 chromatid breaks are not fully understood yet and different hypotheses have been proposed in literature (Parshad et al, 1996;Bryant 1998;Terzoudi et al, 2000). These findings support the view that enhanced chromosomal radiosensitivity observed with the G2 and G0-MN assay in lymphocytes of a high proportion of breast cancer patients, cannot be due to a highly penetrant mutation in one gene, but may be due to low penetrance mutations in different genes involved in the processing of radiation induced DNA damage in G0 and G2 phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these occur very soon after radiation exposure; if left unrepaired may result in longer-term alterations, affecting the maintenance of chromosome stability. However even if DNA damage is repaired in repair proficient cells, signaling of a single DSB triggers the cells to make a genomic rearrangement at the crossover points of a looped chromatin domain, possibly a transcription factory [24,25].…”
Section: Resultsmentioning
confidence: 99%